2021
DOI: 10.1042/cs20210447
|View full text |Cite
|
Sign up to set email alerts
|

Brahma-related gene-1 promotes tubular senescence and renal fibrosis through Wnt/β-catenin/autophagy axis

Abstract: Although accelerated cellular senescence is closely related to the progression of chronic kidney disease (CKD) and renal fibrosis, the underlying mechanisms remain largely unknown. Here, we reported that tubular aberrant expression of Brahma-related gene 1 (BRG1), an enzymatic subunit of the SWltch/Sucrose Non-Fermentable complex, is critically involved in tubular senescence and renal fibrosis. BRG1 was significantly upregulated in the kidneys, predominantly in tubular epithelial cells, of both CKD patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 94 publications
(127 reference statements)
3
28
0
Order By: Relevance
“…Furthermore, uraemic toxins have been implicated in the senescence of proximal tubular cells 193 . Tubular epithelial cell senescence can be induced by inhibition of AMPK–mTOR signalling 194 , activation of the Wnt–β-catenin pathway 195 or overexpression of Wnt9a 196 , and promotes epithelial to mesenchymal transition and consequent fibrosis. α-Klotho, an endogenous antagonist of Wnt–β-catenin signalling, was downregulated in unilateral ureteral obstruction, adriamycin nephropathy, and IRI models of fibrotic kidney disease 197 .…”
Section: Senescence In Kidney Diseasesmentioning
confidence: 99%
“…Furthermore, uraemic toxins have been implicated in the senescence of proximal tubular cells 193 . Tubular epithelial cell senescence can be induced by inhibition of AMPK–mTOR signalling 194 , activation of the Wnt–β-catenin pathway 195 or overexpression of Wnt9a 196 , and promotes epithelial to mesenchymal transition and consequent fibrosis. α-Klotho, an endogenous antagonist of Wnt–β-catenin signalling, was downregulated in unilateral ureteral obstruction, adriamycin nephropathy, and IRI models of fibrotic kidney disease 197 .…”
Section: Senescence In Kidney Diseasesmentioning
confidence: 99%
“…In our model of UUO, the pathogenesis of renal fibrosis involves a complex network orchestrated by necroptosis, oxidative stress, inflammation, TGF-β1, and activation of Wnt/catenin signaling (Jiang et al, 2015;Dai et al, 2020;Jin et al, 2020). Inhibition of necroptosis or Wnt/catenin signaling alleviates UUO-induced renal fibrosis (Xiao et al, 2017;Gong et al, 2021), implying a relationship between necroptosis and Wnt/ β-catenin signaling. Using in vivo and in vitro studies, we observed that overexpressed Wnt3α/β-catenin/GSK-3β protein in UUO rat kidneys and HK-2 cells was inhibited by either Dapa or ICG-001.…”
Section: Discussionmentioning
confidence: 85%
“…Renal fibrosis is the main pathological feature in the development stage of DKD (36). Many factors can lead to renal fibrosis in DKD, such as AGEs, mitochondrial dysfunction, autophagy dysfunction, activation of inflammatory pathway and so on (37)(38)(39). AGEs is considered to be an important factor in the process of DKD renal fibrosis, which can promote the process by stimulating the secretion of oxygen free radicals, cytokines, chemokines, adhesion molecules, TGF-β, CTGF, and other mediators (15,40).…”
Section: Discussionmentioning
confidence: 99%